Pengarusutamaan Gender di Jepang Untuk Mencapai SDG's (Sustainable Development Goals) dalam Perspektif Feminisme Liberal - Nasrullah, Intan Dwi (Journal of Feminism and Gender Studies, 2021)
Japan is one of the countries that has adopted the 2030 sustainable development agenda or SDG's (Sustainability Development Goals) by building an SDG's Promotion Headquarters to achieve balance in the country's development while protecting earth and eliminating poverty. Gender equality is a development target in the SDGs contained in point five. The increase in the elderly and the decline in the birth rate prompted the Japanese Government to take the initiative to increase the role of women in the public. However, the ranking of gender equality in Japan is ranked low globally. Therefore, to achieve the SDGs, the urgent goal that must be done is to address gender equality in Japan by integrating the concept of gender in policy and decision making. In this study, the authors will describe the policies issued by the government in integrating gender and collect data on the gender gap that exists in Japan. By using the concept of gender mainstreaming in liberal feminism perspective, the author takes the initiative to find the causes of the factors that cause gender equality in Japan to be unsuccessful. Therefore, this study will explain some of the obstacles to gender equality by looking at what terms have not been implemented by Japan. The author has succeeded in finding that there are two factors that cause gender equality in Japan to be unsuccessful, there are the lack of commitment and understanding of gender by the government and regulatory agencies and the Gender Responsive Budget (ARG) which has no legal provisions.